Factors affecting willingness to communicate in English among Universiti Kebangsaan Malaysia students - Salim, Muhamad Faizal; Ramdzan Ali, Al Amirul Eimer (Kulliyyah of Languages & Management (KLM), International Islamic University Malaysia, Edu Hub Pagoh, 84600 JHR., 2020)
The Malaysian education system requires students pursuing tertiary education in public universities to take an English placement test, the Malaysian University English Test (MUET) prior entry. This requirement indicates the importance of using and learning the English language to qualify for admission to the university. Having proficiency in English not only enables students to excel in higher education, but also opens a world of opportunities to them. Thus, this study examined the relationship among the variables believed to affect willingness to communicate in English among Universiti Kebangsaan Malaysia (UKM) students. Results depicted that motivation, attitude, communication apprehension and self-perceived communicative competence contribute to willingness to communicate. Meanwhile, the Multiple Regression analysis indicated that the UKM students’ motivation and self-perceived communicative competence had a positive relationship with their willingness to communicate in English. Theoretical and practical implications were discussed to provide insights for future research in this area.